2019
DOI: 10.1021/acs.analchem.9b02263
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Ferrate(VI) as a Highly Efficient and Environmentally Friendly Chemiluminescence Reagent in Acidic Solution

Abstract: Herein we report that the reactions of potassium ferrate (VI) with a number of reductants can produce strong chemiluminescence (CL) in acidic aqueous solution. The CL Spectra were registered and compared with the classical KMnO4 and NaClO-H2O2 CL systems. The characteristic emission peaks at 1268 and 1050 nm were observed, which are consistent to the spectrum obtained from the NaClO–H2O2 system. Additional emission bands at 680 nm further confirmed the formation of singlet oxygen dimers. The high CL intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Three kinds of free radical quenching agents, i.e. , p -benzoquinone as an ˙O 2 − quenching agent, 51 isopropyl alcohol as an ˙OH quenching agent, 52 and tryptophan as an 1 O 2 quenching agent, 53 were applied to the Tar-IrNPs catalysis system, and the changes in absorbance were recorded. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three kinds of free radical quenching agents, i.e. , p -benzoquinone as an ˙O 2 − quenching agent, 51 isopropyl alcohol as an ˙OH quenching agent, 52 and tryptophan as an 1 O 2 quenching agent, 53 were applied to the Tar-IrNPs catalysis system, and the changes in absorbance were recorded. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Free radical quenching experiments were subsequently performed to explore the possible involvement of reactive oxygen species (ROS) in the Tar-IrNPs catalyzed oxidation of PPD. Three kinds of free radical quenching agents, i.e., p-benzoquinone as an O 2 À quenching agent, 51 isopropyl alcohol as an OH quenching agent, 52 and tryptophan as an 1 O 2 quenching agent, 53 were applied to the Tar-IrNPs catalysis system, and the changes in absorbance were recorded. As shown in Fig.…”
Section: The Catalytic Mechanism Of Tar-irnpsmentioning
confidence: 99%
“…It is reported that the redox potential of Fe­(VI) under acidic and alkaline conditions reaches +2.20 V and +0.70 V, respectively . In acidic solutions, Fe­(VI) is considered to be one of the most advanced oxidants since its redox potential is greater than that of ozone (2.08 V) and permanganate (1.67 V). In the past few decades, Fe­(VI) serves as a multifunctional reagent and has been widely used to control inorganic compounds, , heavy metals, and sludge disintegration and dewatering. , Moreover, Fe­(VI) oxidation is promising in eliminating EDCs, such as phenolics, amines, organosulfur compounds, etc. Additionally, the major reductive product of Fe­(VI) is Fe­(OH) 3 , which can work as an adsorbent or coagulant reagent, and further contribute to the removal of organic contaminants …”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] As the reaction time attains 6 h, the solution without NaOH (0 m ) changes to orange, and shows a typical Tyndall effect when a red laser goes through it (Figure S12, Supporting Information), reflecting the formation of Fe(OH) 3 colloid according to Equation (1). [ 17 ] While no obvious changes are observed in the solutions with NaOH ranging from 1 to 12 m , indicative of a different hydrolysis pathway based on Equation (2). As the reaction time continuously proceeds for 12 h, the consumption of FeO 4 2− leads to lighter color of the solutions, in particular, the 1 m NaOH one.…”
Section: Figurementioning
confidence: 99%